Kompetensi Spiritualitas Dalam Pendidikan Agama Kristen Menghadapi Revolusi Industri 4.0 - Br. Ompusunggu, Dorkas (Jurnal Christian Humaniora, 2025)
Spirituality is at the heart of Christian Religious Education. Good spirituality can help educators and students actualize effective and efficient religious education. This study is a qualitative study using a library research approach with written sources as the main data. This study aims to explore and capture the situation of Christian Religious Education in the face of the digital era's development in elementary and secondary education. The dimension of spirituality in Christian Religious Education in the face of the 4th Industrial Revolution can be realized through exemplary behavior, knowledge, skills, empathy, and concern, as well as positive relationships. Furthermore, the pillars of the spiritual dimension consist of resilient and contextual faith, self-integrity in the virtual world, love as a digital lifestyle, spiritual discipline with digital media, critical and wise responses to digital culture, and serving and being a witness in the digital world.